Vitamin d and child health: From the controversy to the novel therapeutic approaches - Diego G. Peroni; Giulia Nuzzi; Roberto Bernardini; Massimo Landi; Alberto Martelli; Carlo Capristo; Pasquale Comberiati (Global Pediatrics, 2024)
Vitamin D (VitD) is a vitamin essential for human life. In addition to its well-known activities on phospho-calcium metabolism and bone mineralization, we start to know its actions at extraskeletal levels, due to the presence of its receptor and the 1α-hydroxylase enzyme in many cells of the body, especially on the cells of the immune system. The controversy on the indications for the use of VitD is extremely debated, perhaps a little less so in pediatric age, where in addition to the undoubted musculoskeletal effects there is much evidence on the immune system effects. In this review, we will examine the actions of VitD and the correlation between its deficit and the development of some pathologies.